Monitoring of Stress in Police Horses - Lelláková M.; Pavľak A.; Florián M.; Lešková L.; Takáčová D.; Kottferová J. (Folia Veterinaria, 2021)
Every year, police horses undergo police training focused on passing difficult obstacles, during which their physical and mental abilities are tested. Using a method of eye movement monitoring, specifically eye blinking and eyelid twitching, we estimated if the training of horses was stressful. The results we found suggested that the training itself, per se does not affect the welfare of police horses; as it is not stressful for them because the gradual training allows the horses to adapt to different types of work or physical activity.